2017
DOI: 10.1111/bju.14017
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of transperineal magnetic resonance imaging/ultrasonography fusion biopsy and transrectal systematic biopsy in biopsy‐naïve patients

Abstract: ObjectivesTo evaluate the value of multiparametric magnetic resonance imaging (mpMRI) in the detection of significant prostate cancer (PCa) and to compare transperineal MRI/ ultrasonography fusion biopsy (fusPbx) with conventional transrectal systematic biopsy (sysPbx) in biopsy-na€ ıve patients. Patients and MethodsThis multicentre, prospective trial investigated biopsy-na€ ıve patients with suspicion of PCa undergoing transperineal fusPbx in combination with transrectal sysPbx (comPbx). The primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 39 publications
(67 reference statements)
4
35
0
Order By: Relevance
“…Particularly, MRI/US fusion‐guided biopsy increased the detection of clinically relevant disease, whilst also decreasing the detection of low‐risk cancer with a reduced number of needed cores . As MRI/US fusion‐guided biopsy alone is currently not advised by most authors and in the current guidelines, an additional 10–12‐core SB is indicated . Consistently there is a reported superior performance of the combination of TB and SB in overall detection rate but also with an associated contamination with insignificant prostate cancer .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Particularly, MRI/US fusion‐guided biopsy increased the detection of clinically relevant disease, whilst also decreasing the detection of low‐risk cancer with a reduced number of needed cores . As MRI/US fusion‐guided biopsy alone is currently not advised by most authors and in the current guidelines, an additional 10–12‐core SB is indicated . Consistently there is a reported superior performance of the combination of TB and SB in overall detection rate but also with an associated contamination with insignificant prostate cancer .…”
Section: Discussionmentioning
confidence: 78%
“…© 2018 The Authors BJU International © 2018 BJU International in the current guidelines, an additional 10-12-core SB is indicated [1,2,12,19]. Consistently there is a reported superior performance of the combination of TB and SB in overall detection rate but also with an associated contamination with insignificant prostate cancer [9,20,21].…”
mentioning
confidence: 89%
“…There are studies reporting a limited additional value of SB in addition to TB [2,22], but other authors also conclude that TB should be combined with SB for improved detection of clinically significant PCa [26][27][28]. However, the integration of MRI/US fusion into the diagnostic pathway in patients with suspicion for PCa with previous negative prostate biopsy led to an increased diagnostic accuracy for the detection of clinically significant PCa (Gleason score ≥3 + 4 = 7a (ISUP 2).…”
Section: Discussionmentioning
confidence: 99%
“…For repeat biopsy situations, MRI guidance has been endorsed by the AUA and the Society of Abdominal Radiology (SAR) . For first‐biopsy situations, available data are not yet clear . However, in the present study the predictive value of TB MCCL held true equally for men undergoing either first or repeat biopsy; thus, an additional reason for pre‐biopsy MRI – the potential for quantifying the index TV – is herein shown.…”
Section: Discussionmentioning
confidence: 55%